Ni-base X-750 합금에서의 단 범위 규칙화 반응 - 김성수; Sungsoo Kim; 정종엽; Jung Jong Yeob; 김영석; Young Suk Kim (대한금속·재료학회지, 58(9), 2020)
The short range ordering (SRO) reaction of the X-750 Ni-base alloy used as a garter spring material for CANDU reactors was systematically investigated through differential scanning calorimeter (DSC) analysis. Water quenching (WQ) after solution annealing (SA) and 20% cold rolled (CR) X-750 were prepared and these samples were subjected to ordering treatment at 475 ℃ for up to 2,160 hours. The WQ and CR specimens showed an exothermic reaction due to the release of entropy formed by the WQ and CR processes, respectively, whereas the ordered WQ and CR specimens exhibited endothermic reactions. The exothermic reaction from the WQ and CR specimens means the SRO reaction occurred. In the WQ specimen, two exothermic reactions at 577 ℃ and 671 ℃ were observed, which corresponds to SRO formation of Ni 2 Cr and CrFe, respectively. The critical temperature and thermal activation energy for these specimens were measured by varying the heating rate. The lattice variation with ordering time at 475 ℃ up to 2,160 hours was measured by XRD using CuKa X-ray. A 0.03-0.09% lattice contraction of the (200) plane occurred, depending on prior treatment condition. We discuss whether a lattice contraction due to SRO reaction may cause voids, providing formation sites for He bubbles in the X-750 garter spring exposed to the operating environment of the CANDU reactor.